Imperial law beyond the edge of empire: Roman court procedure in Chersonesus Taurica - Dolganov, Anna (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 2025)
This article examines a Roman–period enactment from Tauric Chersonesus, a Greek city on the southwestern coast of the Crimean peninsula. By means of this legislative act, the city regulated its judicial administration according to procedures that appear to be modelled on the Roman practice of reiectio iudicum. It is my view that the current understanding of this inscription as reflecting a Greek institutional model of popular jury courts is based on an incorrect reading and interpretation of the text. Here I present a new edition of the inscription with a new assessment of its genre and the judicial procedures outlined in it, which, if correct, have far–reaching implications for Roman legal and institutional history, including the much–debated question of the Roman impact on the institutions of Greek cities. The inscription also furnishes significant new insights into the Roman presence in the northern Black Sea and the de facto extension of the imperial state beyond its official borders into the periphery of the empire.